The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/app112110395
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Mapping of the Inflamed Human Dental Pulp

Abstract: Dental pulp inflammation, caused by the evolution of caries, involves numerous interrelated activities at a cellular and molecular level. Cytokines, proteases, growth factors, and other biomarkers of the host response may take part in dental pulp’s immune defense. The aim of this pilot study was to determine the levels of inflammation, oxidative stress, and extracellular matrix degradation biomarkers in healthy and symptomatic irreversibly inflamed dental pulp samples from children and adolescents. Twenty-thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Accorsi-Mendonca et al ( 2013) using zymography showed higher MMP-9 activity in IRP compared to healthy control, which was confirmed by Sharma et al (2021), used fluorometric assay. Results for total MMP-9 however were not consistent with Gusman et al, 2002 showing significant increase in IRP and no significant change reported by Kritikou et al (2021) (Table S5). Only two of the included studies examined the expression of biomolecules in DF (Brizuela et al, 2020;Zehnder et al, 2011).…”
Section: Diagnostic Accuracy Of Selected Biomoleculesmentioning
confidence: 67%
See 2 more Smart Citations
“…Accorsi-Mendonca et al ( 2013) using zymography showed higher MMP-9 activity in IRP compared to healthy control, which was confirmed by Sharma et al (2021), used fluorometric assay. Results for total MMP-9 however were not consistent with Gusman et al, 2002 showing significant increase in IRP and no significant change reported by Kritikou et al (2021) (Table S5). Only two of the included studies examined the expression of biomolecules in DF (Brizuela et al, 2020;Zehnder et al, 2011).…”
Section: Diagnostic Accuracy Of Selected Biomoleculesmentioning
confidence: 67%
“…A few studies (Accorsi‐Mendonca et al, 2013; Gusman et al, 2002; Kritikou et al, 2021; Sharma et al, 2021), reported on the expression of MMP‐9 in healthy pulps and pulpitis with spontaneous pain, however, the presentation of the data and difference in the method of analysis and the form of MMP‐9 investigated, made it difficult to pool the results. In these studies, Gusman et al (2002) and Accorsi‐Mendonca et al (2013) using zymography showed higher MMP‐9 activity in IRP compared to healthy control, which was confirmed by Sharma et al (2021), used fluorometric assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation